2016
DOI: 10.17507/tpls.0611.05
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Homonymous Set of Words Instruction on Vocabulary Development and Retention of Young Female Elementary Learners in Iranian EFL Context through Metalinguistic Awareness

Abstract: Abstract-Vocabulary learning is indispensable in the process of second language (L2) learning and plays a pivotal role in this regard. At the heart of this issue is the homonymous conflict, which is more problematic and very difficult to deal with. Therefore, the current study was undertaken to cast a little bit of light on homonyms instruction in the area of learners' L2 vocabulary development and retention. In this vein, four intact classes of Iran Language Institute (ILI) comprised of 46 young female EFL le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Only 'lead' is accepted as an English homograph word. The same line of thinking is found in Safataji and Amiryousefi (2016), who assumed that the lexeme Bank is homograph as stated elsewhere in this paper; however, the word Bank is not homograph in linguistics semantics. Rather, it is a homonym.…”
Section: Sentences With Homonymssupporting
confidence: 75%
“…Only 'lead' is accepted as an English homograph word. The same line of thinking is found in Safataji and Amiryousefi (2016), who assumed that the lexeme Bank is homograph as stated elsewhere in this paper; however, the word Bank is not homograph in linguistics semantics. Rather, it is a homonym.…”
Section: Sentences With Homonymssupporting
confidence: 75%
“…In contrast to the pre-test, both learners progressed by 4.8% on average. As Bowyer-Crane et al (2017), Bowyer-Crane et al (2017 and Safataj and Amiryousefi (2016) have argued, achieving good grades has demonstrated that learners have been able to grasp the questions or statements offered in the evaluation. It has also been found out that success in the assessment grade is a direct product of a high to optimum standard of understanding of learning.…”
Section: Findings Discussion and Implication: "Reflecting And Evaluating"mentioning
confidence: 99%
“…The mean score of the total pre-test was 46.6% indicating that in average, the participants were only at a minimum level of achievement. According to Bowyer-Crane et al ( 2017) and Safataj and Amiryousefi (2016), young learners' achievement in assessments are directly related to the level of understanding and the capability to comprehend the given sets of questions or statements. It was also emphasized that a low level of achievement in the pre-test were a clear indication that the participants were having difficulties in constructing simple sentences when it comes to writing task.…”
Section: Tablementioning
confidence: 99%